Gambaran Pengelolaan Limbah Di Puskesmas Kesumadadi Kecamatan Bekri Kabupaten Lampung Tengah Tahun 2025 - Adfan Ridho Fahrezi; Linda Barus; Haris Kadarusman (STIKES Columbia Asia Medan, 2026)
Primary healthcare centers generate both medical and non-medical waste that may pose environmental and public health risks if not properly managed. This study aims to describe the waste management practices at Kesumadadi Public Health Center, Bekri Subdistrict, Central Lampung Regency, in 2025. This research employed a descriptive design conducted in May 2025 at the Kesumadadi Public Health Center. Data were collected through observation and interviews as primary data and secondary data from the health center. Data processing included editing, coding, tabulating, and cleaning, while data analysis was carried out using checklists and questionnaires. The results showed that the segregation of medical and non-medical solid waste was not fully in accordance with standards, waste transportation to temporary storage areas did not use trolleys and lacked designated routes, there was no wastewater treatment facility for liquid waste, and the use of personal protective equipment by staff was not optimal. Waste management practices at the Kesumadadi Public Health Center have not met the required standards, particularly in waste segregation, transportation, liquid waste treatment, and occupational safety, therefore improvements are needed to reduce environmental and health risks.